2001
DOI: 10.1016/s0893-9659(01)80027-6
|View full text |Cite
|
Sign up to set email alerts
|

Upper branch nonstationary modes of the boundary layer due to a rotating disk

Abstract: treatment of asymptotic calculation of upper branch nonstationary instability modes is undertaken in the boundary layer flow due to a rotating disk. A numerical spectral solution of the eigenvalue problem shows good agreement with the results of a rational asymptotic approach, based on the extension of the multideck theory of [l].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Another intriguing point which deserves attention is that, unlike the other boundary layer flows such as the Blasius flow (see [26]), here the stability quantities and as a result the structure of the lower branch modes arise from a balance between the viscous forces and Coriolis effects. Unlike this again, the eigenrelation determining the upper branch modes arises from a balance between various jumps across the critical layers and Stokes layer shift; see for instance [29].…”
Section: Linear Results (δE Terms)mentioning
confidence: 99%
See 1 more Smart Citation
“…Another intriguing point which deserves attention is that, unlike the other boundary layer flows such as the Blasius flow (see [26]), here the stability quantities and as a result the structure of the lower branch modes arise from a balance between the viscous forces and Coriolis effects. Unlike this again, the eigenrelation determining the upper branch modes arises from a balance between various jumps across the critical layers and Stokes layer shift; see for instance [29].…”
Section: Linear Results (δE Terms)mentioning
confidence: 99%
“…Making use of the asymptotic triple-deck theory, the linear and non-linear evolution of the upper branch modes of the rotating-disk boundary layer flow, as far as the orientation of the non-stationary waves is concerned, were examined in [28] and [29]. These modes are the ones naturally observed in the experiments of [12], [17] and [30,31].…”
mentioning
confidence: 99%
“…It was shown that the lower branch corresponds to an effective velocity profile having zero shear stress at the surface of the disk. Making use of the asymptotic triple deck theory, the linear and non-linear evolution of upper branch modes of the rotating disk boundary layer flow, as far as the orientation of the non-stationary waves are concerned, were examined in [32] and [33]. These modes are the ones naturally observed in the experiments of [14], [20] and [34,35].…”
Section: Suction/blowing Influences On the Finite Amplitude Disturbanmentioning
confidence: 99%
“…An intriguing point which deserves attention is that, unlike the other boundary layer flows, like the Blasius flow (see [26]), here the stability quantities found in equations (4.1-4.2), and as a result, the structure of the lower branch modes arise from a balance between the viscous forces and Coriolis effects. The eigenrelation determining the upper branch modes on the other hand arises from a balance between various jumps across the critical layers and Stokes layer shift, see [29]. In figures 3(a-d), a comparison has been made between the computed numerical results of parallel flow approximation (see [7]) and the asymptotic predictions as obtained from equations (4.1-4.2) at a suctions = 1 and blowings = −1.…”
Section: Turkyilmazoglu Zampmentioning
confidence: 99%
“…Both the upper branch and lower branch stationary neutral modes and their asymptotic structures were obtained within the framework of asymptotic expansion at large Reynolds numbers. Making use of the asymptotic triple deck theory, the linear and non-linear evolution of the upper branch modes of the rotating-disk boundary layer flow, as far as the orientation of the non-stationary waves is concerned, were examined in [28] and [29]. These modes are the ones naturally observed in the experiments of [12], [17] and [30,31].…”
Section: Introductionmentioning
confidence: 99%